2003
DOI: 10.1021/ja036801u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Formation of Hydrogen Trioxide (HOOOH) in the Ozonation of 1,2-Diphenylhydrazine and 1,2-Dimethylhydrazine:  An Experimental and Theoretical Investigation

Abstract: Low-temperature (-78 degrees C) ozonation of 1,2-diphenylhydrazine in various oxygen bases as solvents (acetone-d(6), methyl acetate, tert-butyl methyl ether) produced hydrogen trioxide (HOOOH), 1,2-diphenyldiazene, 1,2-diphenyldiazene-N-oxide, and hydrogen peroxide. Ozonation of 1,2-dimethylhydrazine produced besides HOOOH, 1,2-dimethyldiazene, 1,2-dimethyldiazene-N-oxide and hydrogen peroxide, also formic acid and nitromethane. Kinetic and activation parameters for the decomposition of the HOOOH produced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…10 The preparation of HOOOH in organic solvents was proposed from the ozonation of 1,2-diphenylhydrazine in aceton-d 6 O) spectra. 11 They also reported that some alkyl hydrotrioxides (ROOOH) of 1,3-dioxolanes decompose to form HOOOH. 12 In 2004 Wentworth and coworkers prepared HOOOH from the thermal reaction of HOOH with ozone in aceton-d 6 at −78 o C and trioxide was characterized by 1 H NMR spectrum.…”
mentioning
confidence: 99%
“…10 The preparation of HOOOH in organic solvents was proposed from the ozonation of 1,2-diphenylhydrazine in aceton-d 6 O) spectra. 11 They also reported that some alkyl hydrotrioxides (ROOOH) of 1,3-dioxolanes decompose to form HOOOH. 12 In 2004 Wentworth and coworkers prepared HOOOH from the thermal reaction of HOOH with ozone in aceton-d 6 at −78 o C and trioxide was characterized by 1 H NMR spectrum.…”
mentioning
confidence: 99%
“…Some authors assume the intermediate formation of nitroso oxides in processes proceeding without the participation of nitrenes and oxygen 34,90,91 . The ozonolysis of phosphine imines in CH 2 Cl 2 at 195 K yields the corresponding phosphine oxide and nitro compound 90 .…”
Section: Trans-(c S )mentioning
confidence: 99%
“…1,2-Dimethyldiazene (1) reacts with ozone in acetone-d 6 at 195 K to form 1,2-dimethyldiazene-N-oxide (2) (90%) and nitromethane (5) (10%) as the main reaction products 91 . According to the suggested mechanism, intermediate formation of nitroso oxide takes place via the reaction of the azoxy compound with singlet oxygen (Scheme 3).…”
Section: Trans-(c S )mentioning
confidence: 99%
See 1 more Smart Citation
“…200 ms in perchlorate pH 2) precludes the pulsed radiolysis method as being viable for NMR analysis (a single pulse sequence in a typical 1 H NMR experiment shown in Figure 1 is > 25 s). Plesnicar et al [26] have shown that HOOOH is always contaminated with a number of oxidation products of 1,2-diphenylhydrazine and HOOH when the low-temperature ozonation of 1,2-diphenylhydrazine in an organic solvent is employed. Therefore a new methodology was required for the generation of a pure solution of HOOOH.…”
mentioning
confidence: 99%